A Randomized Controlled Pilot Study Comparing the Efficacy of Pulsed Radiofrequency Combined With Exercise Versus Exercise Alone in Pain Relief and Functional Improvement for Chronic Knee Osteoarthritis. Issue 2 (9th September 2020) - Han, Qi; Ma, Yantao; Jia, Peiyu; Wang, Xiaolei; Wang, Bo; Zheng, Yongjun
Abstract: Objectives: To compare the long‐term efficacy between pulsed radiofrequency (PRF) combined with passive stretching (PRF‐PS) exercise and PS exercise alone in reducing pain and improving quadriceps muscle strength and knee function. Methods: Sixty‐two participants were randomly assigned with a 1:1 allocation to the PRF‐PS exercise group or the PS exercise group. Level of pain, muscle strength, and knee function were assessed from baseline to the first, third, and sixth months after treatment using the VAS, peak torque (PT), and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), respectively. Results: There were no significant differences at baseline between the 2 groups. Compared to exercise alone, participants achieved superior efficacy with PRF‐PS in pain relief, improvement of muscle strength, and knee function. Moreover, the improvement of all variables was maintained for a longer period of time in the PRF‐PS group. The reduction in participants' VAS pain intensity scores was superior for PRF‐PS vs. PS with overall estimation (adjusted mean difference: −1.85 cm; 95% confidence interval [CI] −2.25, −1.45 cm; P = 0.000). The increase in participants' PT scores was superior for PRF‐PS vs. PS with overall estimation (adjusted mean difference: 15.53 N. m; 95% CI 7.07, 23.98 N. m; P = 0.000; and 12.62 N. m; 95% CI 0.96, 24.28 N. m; P = 0.000 for PT 60 degrees/s and PT 180 degrees/s, respectively). The reduction in participants' WOMAC scores was superior for PRF‐PS vs. PS with overall estimation (adjusted mean difference: −16.43; 95% CI −22.22, −10.64; P = 0.000). Discussion: The improvement in pain relief and knee function might be associated with restoration of muscle strength after PRF‐PS exercise by overcoming muscle inhibition.